STRATEGI KEPALA SEKOLAH DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MTs NEGERI 1 MALANG - Lana Farhan Alafy Zulmin; Muhammad Hanief; Eko Setiawan (VICRATINA, 2022)
This research which was conducted at MTs Negeri 1 Malang, aims to describe the planning, implementation, and evaluation carried out by the principal in shaping the character of students at MTs Negeri 1 Malang. as for the method used in this study is a qualitative method with the type of approach that is phenomenology. The results of this study are as follows: 1) Planning for the formation of the character of students is carried out from the beginning which includes making a vision and mission that is in line with character education, 2) The implementation of character building to grow the character of students is carried out by habituation of religious activities such as congregational prayers, wiridan , and the sunnah dhuha prayer, 3) The evaluation carried out by the principal is based on which character values are being pursued and the principal also has an obligation to evaluate each learning that takes place. Kata Kunci: strategi, kepala sekolah, karakter peserta didik, MTs Negeri 1 Malang